2012
DOI: 10.1111/j.1755-6686.2012.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Competencies for Practice in Renal Care: A National Delphi Study

Abstract: The aim of this study was to describe essential competencies relevant for professional renal nursing in Sweden. A Delphi study with four rounds was conducted from November 2008 to April 2009. A national sample of renal nurses was used to achieve consensus about the core competencies required. The 43 competencies were reviewed for face validity by external experts representing general nursing, renal nursing, stakeholders and nephrologists. The core competencies were categorised in nine areas according to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…3 A review of the literature found that published papers had developed competencies for nurses working in all areas of nephrology nursing, but none had reviewed their effectiveness (EDTNA/ERCA 2007, Dennison 2011, Lindberg et al 2012, Cowperthwaite et al 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…3 A review of the literature found that published papers had developed competencies for nurses working in all areas of nephrology nursing, but none had reviewed their effectiveness (EDTNA/ERCA 2007, Dennison 2011, Lindberg et al 2012, Cowperthwaite et al 2012).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Consensus approaches, particularly Delphi, and nominal group techniques have long been used in a variety of health settings to solve problems and reach agreement on challenging issues (Fink et al 1984) and to develop clinical guidelines (Murphy et al 1998). Delphi techniques have been commonly used to develop nursing competencies, for example, for renal nurses in Sweden (Lindberg et al 2012), emergency nurses in Australia (O'Connell & Gardner 2012) and family practice nurses in Canada (Moaveni et al 2011). Gibson and Soanes (2000) used the nominal group technique to develop clinical competencies for paediatric oncology nurses, whilst McCance et al (2012) used it in conjunction with a consensus conference to identify key performance indicators for nursing and midwifery.…”
Section: Consensus Approachesmentioning
confidence: 99%
“…Delphi techniques have been commonly used to develop nursing competencies, for example, for renal nurses in Sweden (Lindberg et al . ), emergency nurses in Australia (O'Connell & Gardner ) and family practice nurses in Canada (Moaveni et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…A modified Delphi technique uses both written responses and face-to-face discussions and deliberation to aggregate judgments, analyze results, and reach a workable consensus. This modified Delphi technique is often used by competency researchers across academic disciplines (Barry, Battel-Kirk, & Dempsey, 2012;Johnston et al, 2014;Lindberg, Lundström-Landegren, Johansson, Lidén, & Holm, 2012;Schultz, Koenig, Whiteside, Murray, & National Standardized All-Hazard Disaster Core Competencies Task Force, 2012;Shaikh & Khoja, 2014).…”
Section: Methodsmentioning
confidence: 98%